Corticosteroids reduce vascular ultrasound sensitivity in fast- track pathways (FTP): results from Coventry Multi-Disciplinary FTP for cranial Giant Cell Arteritis. (4th May 2023) - Pinnell, J; Tiivas, C; Mehta, P; Dubey, S
Abstract : Objectives: This study aims to assess the feasibility of the Coventry ultidisciplinary fast-track cranial giant cell arteritis (FTGCA) pathway, which was set up in 2013 in collaboration with vascular physiology and ophthalmology to enable prompt multidisciplinary assessment, including ultrasound (US). This study also looks at the impact of prior corticosteroid (CS) use on the performance of US in real life. Method: Data were collected retrospectively for patients who attended the Coventry FTGCA pathway between 1 January 2014 and 31 December 2017. Patients were identified from US lists and clinical details were obtained from electronic medical records. Results: In total, 620 eligible patients were included in this study. US had a sensitivity of 50%, which improved to nearly 56% in CS-naïve patients. The median duration of CS use prior to US was 2 days, and sensitivity was around 46% in this group. The specificity of US was > 96%, and CS use was avoided completely in 345 patients (56%). CSs natively impacted on the utility of US, with US more likely to be false negative. Conclusions: This novel multidisciplinary pathway demonstrates excellent feasibility and minimizes the use of CSs in patients without giant cell arteritis. US was performed promptly, was cost effective- and had reassuring real-life sensitivity and specificity in this cohort, with excellent patient feedback. CS-naïve patients showed higher sensitivity for US despite the short duration of CS use.